Transferring Resilience Metrics: Evaluating the Adaptability of Resilience Metrics from Different Domains for Assessing Vehicle Resilience - Hersi, Zakaria; Bångsbo, Erik (My University, 2024)
Recent advancements in the automotive domain have made vehicles more dependent on the Internet to make the driving experience smoother. This increases the attack surface as this new connectivity can be targeted and it cannot be assumed that these attack surfaces are secure. To still build secure systems resilience can be used. Resilience is, the extent a system can sustain attacks and still be functional, to a certain degree. Currently there exists no metrics for cyber security resilience in vehicular design. This thesis aims to explore existing metrics in related domain to investigate the possibility of adapting those metrics into the automotive domain. To this end, a literature study is performed with 10 investigated papers with 244 metrics found. Attack-injection experiments are performed using the MODIFI tool and Simulink models on the adapted Health Index metric to evaluate the difficulty and practicality of adapting metrics. We found that it is possible to adapt resilience metrics from related domains into the automotive domain. However, depending on the complexity of the metric it can be difficult to adapt it as some modifications may be necessary to be able to use it within the automotive domain.
Keywords: cybersecurity, resilience, survey, automotive security, safety-critical systems.